Distinct roles of ADIPOR1 and ADIPOR2: A pan-cancer analysis - Chen, Zhuoyuan; Yang, Huiqin; Ren, Yunfeng; Yang, Ze; Huang, Jiazheng; Li, Cheng; Xiong, Ying; Yu, Bin (Frontiers in Endocrinology, 2023)
Adiponectin Receptor 1 (ADIPOR1) and Adiponectin Receptor 2 (ADIPOR2) encoded by ADIPOR1 and ADIPOR2 genes respectively, are the receptors of adiponectin secreted by adipose tissue. Increased studies have identified the vital role of adipose tissue in various diseases, including cancers. Hence, there is an urgent need to explore the roles of AdipoR1 and AdipoR2 in cancers. Here, we conducted a comprehensive pan-cancer analysis for the roles of AdipoR1 and AdipoR2 via several public databases. Both ADIPOR1 and ADIPOR2 were dysregulated in most cancers, but their genomic alteration frequencies were low. In addition, they were also correlated with the prognosis of some cancers. In addition, ADIPOR1/2 displayed significant associations with cancer stemness, tumor immune microenvironment, immune checkpoint genes (especially CD274 and NRP1), and drug sensitivity. In summary, our study revealed that ADIPOR1 and ADIPOR2 played critical roles in diverse cancers, and it is a potential strategy to treat tumors through targeting ADIPOR1 and ADIPOR2.